Pemanfaatan Candi Lumbung sebagai Sumber Pembelajaran IPS: The Utilization of Lumbung Temple as a Learning Resource for Social Studies Education - Eldisma Riantika; Khoirun Nikmah (Moderasi: Jurnal Studi Ilmu Pengetahuan Sosial, 2025)
Lumbung Temple, a Buddhist temple located in the Prambanan area, is thought to have been built in the 9th century AD and has the original name “Welfare Temple” due to the statue of the Goddess of Prosperity at its entrance. With a typical architecture of one main temple surrounded by 16 ancillary temples, this temple functions as a place of meditation and asceticism. This research aims to examine the utilization of Lumbung Temple as a social studies learning resource through a qualitative approach involving interviews, observation, documentation, and literature study. The results show that this temple can be used as a social studies learning resource through three strategies: surveys, field trips, and inviting sources. These strategies enable students to develop historical understanding, appreciative attitude towards cultural heritage, as well as social skills through direct experience relevant to local wisdom.